IMPLEMENTASI NILAI RELIGIUSITAS DAN TOLERANSI DALAM PEMBERDAYAAN MASYARAKAT PADA JAMAAH MASJID AL-HIKMAH SIDOMUKTI SALATIGA - Imam Sutomo (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2014)
This study is specifically aims to 1) describe the implementation of Islamicvalues as well as tolerance in the people’s lives; and 2) explore the potential synergy of the contributions driven by both values (religiousity and tolerance) in the community empowerment. The findings of the research are: 1)the internalization of the religious values happens when there is a harmony in the work as done cooperatively between the committee in charge of the congregation activities and the person involve in the activities to revive the mosque activities as a whole; 2)the development of the values of tolerance proven empirically in people’s openness to variety of individuals’ praying rituals and the harmonious relationship between the members of the congregation andthe members of the local communities, including non-Moslem people; and 3) the synergy of the implementation of religious values and tolerance can be clearly seen in the empowering of the members of the congregation in the aspect of social life (through education and economic development) and their freedom to participate in the recent election based on each member’s political orientation.